2016
DOI: 10.1002/cne.24054
|View full text |Cite
|
Sign up to set email alerts
|

Individual mediodorsal thalamic neurons project to multiple areas of the rat prefrontal cortex: A single neuron‐tracing study using virus vectors

Abstract: The prefrontal cortex has an important role in a variety of cognitive and executive processes, and is generally defined by its reciprocal connections with the mediodorsal thalamic nucleus (MD). The rat MD is mainly subdivided into three segments, the medial (MDm), central (MDc), and lateral (MDl) divisions, on the basis of the cytoarchitecture and chemoarchitecture. The MD segments are known to topographically project to multiple prefrontal areas at the population level: the MDm mainly to the prelimbic, infral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
76
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 59 publications
12
76
0
Order By: Relevance
“…Recently, single‐cell tracing studies of the above three higher‐order thalamic regions demonstrated that single neurons of these thalamic regions formed multiple axon arbors in the different cortical areas (Ohno et al, ; Nakamura et al, ; Kuramoto et al, ). Accordingly, the formation of multiple axon arbors may be common characteristics as higher‐order thalamic nuclei neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, single‐cell tracing studies of the above three higher‐order thalamic regions demonstrated that single neurons of these thalamic regions formed multiple axon arbors in the different cortical areas (Ohno et al, ; Nakamura et al, ; Kuramoto et al, ). Accordingly, the formation of multiple axon arbors may be common characteristics as higher‐order thalamic nuclei neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the corticothalamic excitatory input may function as a driver input for the ventral Sm. Similarly, several thalamic regions, such as the anterior region of the posterior nuclei, the lateral subdivision of the lateral posterior nucleus, and mediodorsal nucleus, have been reported to show few or very weak VGluT2 immunoreactivity (Kaneko, Fujiyama, & Hioki, ; Ohno et al, ; Nakamura, Hioki, Furuta, & Kaneko, ; Kuramoto et al, ). These three thalamic regions have been considered to be higher‐order thalamic nuclei (Varela, ), and suggested to receive driver inputs from layer 5 of the cerebral cortex (Groenewegen, ; Bourassa & Deschênes, ; Veinante, Laballée, & Deschênes, ).…”
Section: Discussionmentioning
confidence: 99%
“…Rose and Woolsey originally proposed the terminal fields of projections from the mediodorsal nucleus of the thalamus as a criterion for defining the prefrontal cortex [82]. Axons from the lateral division of MD thalamus project to M2 [19,83,84]. On the whole, MD thalamic projections can be found in M2 as well as orbital, prelimbic, infralimbic, anterior cingulate, and agranular insular regions, but they are absent in primary motor and sensory cortices in mice [85].…”
Section: Afferent Connections From Diverse Cortical and Thalamic Sourcesmentioning
confidence: 99%
“…Anatomically, thalamic output to the cortex is quite variable, with only a minority of thalamic circuits exhibiting a topographic and spatially restricted innervation of a single cortical target [30,31]. Additionally, many thalamic circuits receive convergent inputs from a single or multiple cortical regions that do not appear to be compatible with the idea of topographic relay [32].…”
Section: Thalamic Regulation Of Functional Cortical Connectivitymentioning
confidence: 99%